Sweden : Financial Sector Assessment Program-Technical Note- Banking Regulation and Supervision. (IMF Staff Country Reports; Country Report ;, 2017)
This Technical Note evaluates banking regulation and supervision in Sweden. The Finansinspektionen (Financial Supervisory Authority, FI) has made considerable progress developing supervisory approaches and techniques, particularly structured risk assessments for the four large banking groups. Concerns raised in the 2011 Financial Stability Assessment Program regarding insufficient granularity and frequency of reporting by supervised institutions has been addressed, starting in the third quarter of 2014. The FI has also implemented a new system for management of banking and insurance supervisory data. The IMF staff expressed satisfaction with the system's functionality and flexibility to produce custom reports. The work to put in place a standardized set of internal screening and analytical reports, however, is ongoing.